Uma caracterização do saber profissional do professor que ensinava aritmética a partir de exemplares da Revista de Ensino (1902-1930) - Santos, Rejane (2022)
This plot presents the result of a proposal that aimed to characterize the professional knowledge of the teacher who taught arithmetic from copies of the Revista de Ensino published in the states of São Paulo and Alagoas between 1902 and 1930. , studies were used that discuss the constitution of the teacher's professional knowledge, adopted by Valente (2018,2019) and Morais, Bertini and Valente (2021), which encompass an arithmetic to teach and to teach. It is also noteworthy that the elements of an arithmetic of teaching were also taken as a guide, for understanding that, as magazines are a vehicle for the circulation of proposals to be applied, they bring in their core proposals articulated from the classroom and for the classroom. In this way, the analysis categories sequence, graduation, meaning, exercises and problems were adopted as a lens for the examination of the twenty articles located, making it possible to immediately identify a sequence that can be summarized as counting and numbers, fraction and operations. In relation to the internal sequence, elements of distance were identified, such as how to start counting the ten or the numbers up to twelve. In the case of fractions, sometimes they started with decimal fractions and sometimes with ordinary fractions. It was also possible to observe a graduation that contemplated the first notions about quantities using objects such as pebbles and oranges. Subsequently, these quantities should be improved by counting up to five of these objects, followed by teaching the ten using materials such as Parker's Letters, the mechanical counter, the lathe, etc. The operations were worked through terms such as “put” and “take away” to give meaning to addition and subtraction. As for the grading of fractions, the first proposals would appear still in the teaching of divisions into equal parts and without remainder, initiated through the sharing of objects. After having established its main concepts, the graduation proposed for the fractions did not contemplate the use of materials to be worked on the operations, so that before the arithmetic notations appear, there were only proposals for oral problems and useful in the student's daily life. . The proposals presented for teaching were based on evidence of the intuitive method, so that through guidelines on the use of teaching materials, in addition to problems and oral and practical exercises, it is possible to verify this statement. Finally, it was evidenced that by carrying out this type of approach the teacher could provide his student with the perception from the known to the unknown, exploring a teaching based on the knowledge of things and experiences.